2017
DOI: 10.2807/1560-7917.es.2017.22.31.30584
|View full text |Cite
|
Sign up to set email alerts
|

Novel mcr-3 variant, encoding mobile colistin resistance, in an ST131 Escherichia coli isolate from bloodstream infection, Denmark, 2014

Abstract: A novel variant of the plasmid-borne colistin resistance gene mcr-3 was detected on an IncHI2 plasmid in an ST131 CTX-M-55-producing Escherichia coli isolate from a Danish patient with bloodstream infection in 2014. The discovery of novel plasmid-borne genes conferring resistance to colistin is of special interest since colistin has reemerged as an important drug in the treatment of infections with multidrug-resistant Gram-negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 13 publications
1
47
1
Order By: Relevance
“…Our study has shown that the mcr-1 , mcr-2 and mcr-3 occurred widely in pigs and poultry from China (Table 1, Tables S1–S5). The prevalences we found were considerably higher than those previously reported in China and elsewhere in the world 326,29,30 which were based on the presence of the mcr in bacterial isolates. Bacterial isolation, however, is cumbersome, costly, and time-consuming, and it is also selective in that samples must be appropriately collected, transported and stored to maximize the number of viable bacteria with the mcr that can be selectively cultured.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Our study has shown that the mcr-1 , mcr-2 and mcr-3 occurred widely in pigs and poultry from China (Table 1, Tables S1–S5). The prevalences we found were considerably higher than those previously reported in China and elsewhere in the world 326,29,30 which were based on the presence of the mcr in bacterial isolates. Bacterial isolation, however, is cumbersome, costly, and time-consuming, and it is also selective in that samples must be appropriately collected, transported and stored to maximize the number of viable bacteria with the mcr that can be selectively cultured.…”
Section: Discussioncontrasting
confidence: 91%
“…coli in China 23 and later shown to be present in bacteria isolated from humans from Denmark, chickens from China, cattle from Spain 19,20,2426 , and flies in China 31 . Our findings indicate that the gene is quite widespread, as we found it in samples from pigs and poultry from many provinces in China, albeit at low prevalence in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of resistance to 3GCs in pathogenic E. coli can be attributed to the beta-lactamase Cefotaxime-Munich (bla CTX-M ) family of resistance genes (Livermore and Hawkey, 2005), with the remainder accounted for by the bla TEM and bla OXA families. The bla CTX-M mediated ESBL resistance is frequently recorded in ExPEC strains of E. coli and is particularly associated with the ST131 lineage (Roer et al, 2017, Harris et al, 2018. Group 9 bla CTX-M variants are present on mobile genetic elements within E. coli ST131, with bla CTX-M-27 being responsible for upwards of 10% of ESBL resistance in clinical urological E. coli infections (Ghosh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic findings of mcr‐1 carrying isolates have previously been reported from three other Nordic countries, namely Sweden, Norway and Denmark . After the first wave of mcr‐1 reports, several countries including Denmark from the Nordic countries, have identified isolates carrying new gene variants of mcr gene (currently mcr‐1 to mcr‐5 ) . In Finland, the overall antimicrobial resistance level has remained relatively low, and use of colistin is reserved for only very rare clinical indications.…”
mentioning
confidence: 99%